STEP-BY-STEP INTEGRATION OF CULTURAL MOTIFS IN ART EDUCATION FOR GRADES 5–7 - Boboqulov Javohir Hamzayevich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the methodological foundations of integrating cultural motifs step by step into art education for students in grades 5–7. The study emphasizes the importance of national and cultural identity in developing students’ artistic, aesthetic, and creative competencies. By using cultural symbols, patterns, and traditional artistic expressions in a gradual and structured manner, teachers can foster students’ understanding of heritage while enhancing their imagination and visual literacy. The research highlights how incorporating cultural elements into classroom activities contributes to the development of emotional sensitivity, aesthetic taste, and respect for national traditions. The proposed model aims to ensure the continuity of cultural values through art education and to nurture a sense of belonging among young learners.